A Reinforcement Learning Algorithm Based on Policy Iteration for Average Reward Empirical Results with Yield Management and Convergence Analysis. - Gosavi, Abhijit (Machine learning.)
We present a Reinforcement Learning (RL) algorithm based on policy iteration for solving average reward Markov and semi-Markov decision problems. In the literature on discounted reward RL, algorithms based on policy iteration and actor-critic algorithms have appeared. Our algorithm is an asynchronous, model-free algorithm (which can be used on large-scale problems) that hinges on the idea of computing the value function of a given policy and searching over policy space. In the applied operations research community, RL has been used to derive good solutions to problems previously considered intractable. Hence in this paper, we have tested the proposed algorithm on a commercially significant case study related to a real-world problem from the airline industry. It focuses on yield management, which has been hailed as the key factor for generating profits in the airline industry. In the experiments conducted, we use our algorithm with a nearest-neighbor approach to tackle a large state space. We also present a convergence analysis of the algorithm via an ordinary differential equation method.